Phagocytic ability of neutrophils and monocytes in neonates - Athanasios Filias; Γεώργιος Θεοδώρου; Sofia Mouzopoulou; Anastasia Varvarigou; S Mantagos; Μαρίνα Καρακάντζα (2011)
Abstract Background Infections by a variety of pathogens are a significant cause of morbidity and mortality during perinatal period. The susceptibility of neonates to bacterial infections has been attributed to immaturity of innate immunity. It is considered that one of the impaired mechanisms is the phagocytic function of neutrophils and monocytes. The purpose of the present study was to investigate the phagocytic ability of neonates at birth. Methods The phagocytic ability of neutrophils and monocytes of 42 neonates was determined using the Phagotest flow cytometry method, that assesses the intake of E. Coli by phagocytes, in cord blood and in peripheral blood 3 days after birth. Fifteen healthy adults were included in the study as controls. Results The phagocytic ability of neutrophils in the cord blood of neonates was significantly reduced compared to adults. The 3 rd postnatal day the reduction of phagocytic ability of neutrophils was no longer significant compared to adults. The phagocytic ability of monocytes did not show any difference from that of adults either at birth or the 3 rd postnatal day. Conclusions Our findings indicate that the intake of E. Coli by phagocytes is impaired at birth in both preterm and full term neonates compared to adults. This defect is transient, with the phagocytic ability in neonates reaching that of the adults 3 days after birth.